Surface Characterization of Asymmetric Bi-Soft Segment Poly(ester urethane urea) Membranes for Blood-Oxygenation Medical Devices - Mónica Faria; Vítor Geraldes; Maria Norberta de Pinho (International Journal of Biomaterials)
Asymmetric bi-soft segment poly(ester urethane urea) (PEUU) membranes containing polycaprolactone (PCL) as a second soft segment are synthesized with PCL-diol ranging from 0% to 15% (w/w). Bulk and surface characteristics of the PEUU membranes were investigated by scanning electron microscopy (SEM), static water contact angles, and surface streaming potentials and were correlated to hemocompatibility properties, namely, hemolysis and thrombosis degrees. SEM analysis reveals PEUU membranes with asymmetric cross-sections and top dense surfaces with distinct morphologies. The increase in PCL-diol content yields PEUU membranes with blood-contacting surfaces that are smoother, more hydrophilic, and with higher maximum zeta potentials. The results obtained in this work give no evidence of a correlation between hydrophilicity/zeta potentials and the hemolysis/thrombosis degree of blood-contacting surfaces of the PEUU membranes. In contrast, other hemocompatibility aspects reveal that the more hydrophilic membranes are associated with lower platelet deposition and inhibition of extreme states of platelet activation.